Mechanisms of knowledge sharing in open source software projects: a comparison of Chinese and Western practice. (2016) - Chen, Xiaohong; Probert, David; Zhou, Yuan; Su, Jun
This paper aims to analyse the key factors influencing knowledge sharing in open source software (OSS) projects. Four deep cases are analysed to develop a conceptual framework based on within-case and cross-case analysis. In terms of data collection, online (including Skype meeting, email, email-list, internet relay chat (IRC), forum, group meeting, etc.) and offline (mainly with face-to-face discussion) activities are two major platforms. The research framework is that distributed innovation (independent variable) will influence shared knowledge (medium variable) and continue to affect the performance of OSS projects (dependent variable). During distributed innovation, developers located on the supply side will affect the shared knowledge from the aspects of participative motivation, social networks and organisational culture. Meanwhile, users situated on the demand side will function from the view of user innovation. Differences and similarities of China and the West towards OSS Projects are derived from the evidence, and some implications for the Chinese approach are proposed.